Comparison of the ViOptix Intra.Ox Near Infrared Tissue Spectrometer and Indocyanine Green Angiography in a Porcine Bowel Model - Khavanin, Nima; Almaazmi, Hamda; Darrach, Halley; Kraenzlin, Franca; Safar, Bashar; Sacks, Justin M. (Journal of Reconstructive Microsurgery, 2020)
Background This study aims to directly compare measurements of tissue oxygenation obtained using the Intra.Ox (Vioptix Inc., Fremont, CA) near infrared spectrometer with the perfusion assessment of the indocyanine green (ICG)-based SPY Elite imaging system (Stryker Co., Kalamazoo, MI) in a porcine bowel model.Methods Two live minipigs underwent laparotomy and isolation of a 30-cm segment of a large bowel. Standardized oximetry measurements were taken along the segment of bowel immediately before, after, and serially for 30 minutes following transection. A 0.5 mg/kg dose of ICG was then injected intravenously and the SPY Elite system was used to visualize and quantify tissue perfusion. Pearson's correlation coefficients were calculated using the outcomes.Results Transected and ligated bowel yielded mean Intra.Ox measurements of 61% oxygenation at the proximal base of the limb and 27.8% at the distal edges. Analysis of the relative ICG fluorescence using the SPY Elite's proprietary software yielded perfusion estimates of 64.8% proximally and 6.8% distally. Intra.Ox and SPY Elite measurements demonstrate a Pearson product–moment correlation of 0.929. Repeat measurements at 15-mm intervals along the tissue yielded decreasing Intra.Ox measurements along the length of the flap that correlate to SPY Elite measurements (r = 0.645).Conclusion Both the Intra.Ox and the SPY detected clinically relevant changes in bowel oxygenation following transection and ligation. The use of intravenous ICG dye did not appear to affect measurements of tissue oxygenation obtained using the Intra.Ox.
Keywords: necrosis; perfusion; anastomosis; technology; oxygenation